Arthropod Insect Communities in Several Different Habitats - Anggita, Sri Ayu (Faculty of Agriculture, Tompotika Luwuk University, 2025)
Interactions between biotic and abiotic components in ecosystems influence insect mortality, natality, and dispersal, thereby making species composition dynamic. The presence and abundance of arthropods in agricultural systems cannot be precisely predicted, as they are affected by numerous factors such as cropping practices, habitat type, plant age, and interspecific interactions among arthropods. This study aimed to examine the diversity, abundance, and community composition of arthropods across four agricultural habitat types: maize, soybean, weeds, and soil surface. Arthropod samples were collected through direct observation, sweep netting, and pitfall traps. The findings revealed that insects from the order Hemiptera had the highest abundance in comparison to other orders, with 51 individuals recorded on maize and 409 on soybean. In contrast, 244 insects were found on weeds, dominated by the order Diptera. On the soil surface, a total of 482 insects were collected, predominantly from the order Collembola. The Collembola order exhibited the lowest values in terms of relative diversity index (H′), dominance (D), and evenness (E) compared to other habitats. The Bray–Curtis similarity index between soybean and weed habitats was the highest (0.205), indicating a greater similarity in arthropod composition between these two habitats. Conversely, the lowest similarity value (0.043) was observed between soybean and soil surface habitats, suggesting a greater difference in arthropod community composition.